Effect of resilience intervention on dispositional optimism on regular battalion soldiers in Colombia - Alvarán López, Sandra Milena; Bedoya Mejía, Sebastián; Henao Valencia, Ceneida; Velásquez Correa, Juan Carlos; Grisales-Romero, Hugo de Jesús (Pensando Psicología, 2020)
Objective: to evaluate the effect of the strategy of psychosocial workshops on dispositional optimism in regular soldiers of a battalion, of regular soldiers from Colombia. Methodology: a quasi-experimental pretest-posttest study was designed where each soldier was his own control. The sample consisted of 196 regular soldiers who were administered a questionnaire on dispositional optimism, based on 21 items, which measures this in one dimension. To observe differences obtained in the mean scores in the pretest and in the posttest, 95% confidence intervals were used for related samples. The effect size was calculated according to the indicators obtained in the pretest and in the posttest. The McNemar test allowed us to assess the significance of the changes in total optimism before and after the intervention. The SPSS statistical program was used to obtain the results. Results: the study recruited 88 regular soldiers with dispositional optimism (44.9%) and 108 with pessimism (55.1%) before the intervention; After that, it was observed that of the 108 who scored pessimistically in the pre-test, in the post-test 45 (41.7%) obtained scores that allowed them to be classified as optimistic. The intervention did not have a significant effect from a statistical point of view, but the findings suggest an important effect from the clinical point of view in the change from pessimism to dispositional optimism (McNemar test, p = 0.510). Conclusions: the intervention strategy, psychosocial workshops, must be reassessed to generate greater changes in the clinical and statistical aspects.